2005
DOI: 10.4049/jimmunol.174.12.7558
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Agonist Ameliorates Established Allergic Airway Inflammation by Promoting Th1 Response and Not via Regulatory T Cells

Abstract: TLRs are primary sensors of both innate and adaptive immune systems, where they play a pivotal role in the response directed against structurally conserved components of pathogens. Synthetic bacterial lipopeptide Pam3CSK4 is a TLR2 agonist capable of modulating Th1 and Th2 responses. This study examines the therapeutic effect of Pam3CSK4 in established airway inflammation in a murine model of asthma. In mice previously sensitized and challenged with OVA, Pam3CSK4 given i.p. markedly reduced the total inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
111
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 38 publications
9
111
2
3
Order By: Relevance
“…Previous studies have evaluated the effect of TLR2 signaling on allergic diseases, but the results are conflicting. In our model, triggering of TLR2 with Pam3CSK4 showed a beneficial antiallergic effect on allergic rhinitis, which is consistent with several pre- vious studies (Akdis et al, 2003;Patel et al, 2005;Revets et al, 2005). The mechanism of its antiallergic effect is still elusive.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous studies have evaluated the effect of TLR2 signaling on allergic diseases, but the results are conflicting. In our model, triggering of TLR2 with Pam3CSK4 showed a beneficial antiallergic effect on allergic rhinitis, which is consistent with several pre- vious studies (Akdis et al, 2003;Patel et al, 2005;Revets et al, 2005). The mechanism of its antiallergic effect is still elusive.…”
Section: Discussionsupporting
confidence: 74%
“…TLR2 has been reported as an important pattern recognition receptor (PRR) on regulatory T cells (Tregs) and the CD4 + CD25 + Treg subset in TLR2-deficient mice is significantly reduced compared to wild type mice, suggesting a relationship between Tregs and TLR2 (Sutmuller et al, 2006). However, Patel et al(2005) reported that, by using blocking antibodies, the antiallergic effect of Pam3CSK4 was independent of IL-10 or TGF-β, but critically dependent on IL-12, and hence, Tregs are unlikely to play an important role in the therapeutic effect of Pam3CSK4. Therefore, it was suggested that TLR2 activation by Pam3CSK4 stimulates the antigen-presenting cells to secrete cytokines such as IL-12 and IFN-γ, which causes the enhancement of IFN-γ synthesis by T cells, resulting in decreased Th2 cell differentiation and attenuated eosinophilic airways inflammation, which might be the same as activation of TLR9 with CpG DNA (Kline, 2007).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…When lipopeptide is used as an adjuvant with ovalbumin, it can exacerbate experimental asthma and produce an associated systemic Th2 response, which, unlike LPS, is not dose dependent (13). Another study investigated the effect of TLR2 agonists on established airway inflammation and discovered that lipopeptide actually attenuated disease, and this was associated with an increase in IFN-␥ and therefore predominant Th1-type response (11). The route of exposure to a given ligand has been shown to be important in influencing the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…It also has been demonstrated that activation of dendritic cells by specific TLR ligands can influence the development of an adaptive immune response both in vivo (7) and in vitro (11)(12)(13). TLR2 can be found on professional immune cells, including neutrophils, macrophages, and dendritic cells, but also on stromal cells throughout the body (14).…”
mentioning
confidence: 99%